Synthesis and characterization of multiferroic magnetoelectric ceramic composites - Coondoo, Indrani (2022)
Ceramic composites with composition (1−x)[Ba0.85Ca0.15Zr0.1Ti0.9O3] − x[Ni0.7Zn0.3Fe2O4], (0 ≤ x ≤ 100 wt%) were prepared using solid state route. Structural and microstructural analysis confirmed the coexistence of ferroelectric (BCZT) and magnetostrictive (NZFO) phases without any detectable presence of impurity/secondary phases. The composites exhibited ferroelectric, magnetic properties and magnetoelectric coupling responses. Highest coupling coefficient was obtained for composite with 50 wt% NZFO.